2017
DOI: 10.3892/etm.2017.4387
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-186 inhibits prostate cancer cell proliferation and tumor growth by targeting YY1 and CDK6

Abstract: microRNAs (miRNAs) are known to be important in tumor initiation and progression. Recent studies have demonstrated that miR-186 is critical in several types of cancer, including human non-small cell lung cancer, bladder cancer and pancreatic ductal adenocarcinoma. However, the functions of miR-186 in prostate cancer (PCa) are still unclear. In the present study, downregulation of miR-186 in PCa cells was detected when compared with the normal prostate cell line. When miR-186 overexpressed in PCa cells, cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…After cDNA synthesis using the reverse transcription kit (Promega, Madison, WI), the expression level of YY1 mRNA was quantified by RT‐PCR with Power SYBR Green PCR Master Mix (Carlsbad, CA) and GAPDH as a control for normalization. The sequence of YY1 primer was as follows: YY1, 5′‐CAACAAGAAGTGGGAGCA‐3′ and 3′‐CCACTGTCTCATGGTCAA‐5′ (Lu et al, ). The 2 −ΔΔ C t method was performed to calculate the relative expression of target genes.…”
Section: Methodsmentioning
confidence: 99%
“…After cDNA synthesis using the reverse transcription kit (Promega, Madison, WI), the expression level of YY1 mRNA was quantified by RT‐PCR with Power SYBR Green PCR Master Mix (Carlsbad, CA) and GAPDH as a control for normalization. The sequence of YY1 primer was as follows: YY1, 5′‐CAACAAGAAGTGGGAGCA‐3′ and 3′‐CCACTGTCTCATGGTCAA‐5′ (Lu et al, ). The 2 −ΔΔ C t method was performed to calculate the relative expression of target genes.…”
Section: Methodsmentioning
confidence: 99%
“…Lu et al . found that miR‐186, which inhibits prostate cancer cell growth in vitro and tumors in nude mice, downregulates YY1 expression and that of cyclin‐dependent kinase 6 (cdk6) by binding to their 3′ UTRs …”
Section: Yy1 and Tumor Growthmentioning
confidence: 99%
“…miRNA is a non-coding RNA closely related to the development and progression of tumors, and its role in prostate cancer has been widely discussed in recent years (11). There are various miRNA targets that can be used for the diagnosis and treatment of prostate cancer, with more tumor suppressor genes and fewer oncogenes (12,13). A study has shown that the upregulation of miR-101 inhibits the proliferation and invasion of prostate cancer cell line Du145 by inhibiting its target gene EZH2 (14).…”
Section: Discussionmentioning
confidence: 99%